Stroke in Young Adults: The Role of Paradoxical Embolism - Chant, Harvey; McCollum, Charles (Thrombosis and Haemostasis, 2001)
Stroke in young adults may be devastating and frequently no cause can be found. However, there is ample literature to suggest an association between cryptogenic stroke in young people and paradoxical embolisation via a venous to arterial circulation shunt (v-aCS), commonly due to patent foramen ovale (PFO). Although paradoxical embolisation is assumed to be a rare event, this review suggests that it is an important or even dominant cause of stroke in young people and that a transcranial Doppler (TCD) technique may be the investigation of choice to identify v-aCS.Appendix I, II on pp. 26-7
Keywords: Venous to arterial circulation shunt; foramen ovale; transcranial doppler; ischaemic stroke